ENSINO DE ADMINISTRAÇÃO NO CONTEXTO DA EDUCAÇÃO A DISTÂNCIA: ESTUDO COM TUTORES DE UMA INSTITUIÇÃO ESTADUAL DO RIO DE JANEIRO - CAMPOS, GLAUCO CARVALHO (2019)
The Era of Information promoted by the advancement of technology brings new relationships in society. People and organizations use technology to communicate. The virtual community emerges. To the same extent, the country's formal education system adapts to this reality and educational institutes begin to offer undergraduate courses in the distance modality. E-learning has demanded the attention of scholars about this new teaching modality that discuss: teacher training, mediation, mentoring, methodologies and teaching practices. Each year, it is noticed a growing movement of vacancies in online graduation. E-learning brings new elements to the context of education, such as the redefinition of time and space, the promotion of the socialization of teaching that is offered through campuses elsewhere. In this scenario, the Universidade Federal Rural do Rio de Janeiro, through the CEDERJ consortium enables the free higher education in Management cource through 14 campuses located in the capital and in the interior of the state of Rio de Janeiro. Thinking about E-learning means revisiting the relationship between teachers and students, the use of available materials and resources, the format of courses that are feasible through online teaching platforms, the use of ICT, the construction of learning in a collective way and the possibility of creating the autonomy of learning in the student. In this context, Management course is one of the most sought-after courses for undergraduate students in the country and its expression is also perceived in E-learning courses. The teaching in Management cource, in turn, becomes a challenge since the Management professionals are bachelorship and do not have pedagogical training to work in the teaching profession. Thus, the problem of this research is to question how the training process is given and the teaching practice of the Management professional who operates in E-learning through qualitative research, using the semi-structured interview as an instrument of data collection and relying on content analysis, the objective of this work was to identify the aspects of teacher training who work in the undergraduate course in Management cource of the CEDERJ consortium, we also sought to identify the competencies, skills and attitudes of teachers to develop a pedagogical practice focused on E-learning, besides the description of educational practices focused For the teaching exercise its practice. The results show that they exercise double careers both in organizations and in the exercise of teaching, which is a positive fact to contextualize the professional teaching practice. However, there are gaps in the pedagogical training of the graduates who work in teaching and many of them promote only continuous training directed to the labor market, which makes the teaching practice more difficult. Many of them possess the skills, skills and attitudes towards teaching, however, the available pedagogical tools are used in a reduced way. The mediation between the tutors and the students and the resources was a prominent point and that demonstrates a seriousness of them in the conduction of the teaching profession. It was also perceived a feeling of non-completeness in the exercise of teaching by the interviewees who perceive their fragmented function, in addition to the lack of a closer pedagogical alignment between UFRRJ and the tutors of the CEDERJ consortium. The limitation of this research is due to the fact that it was performed in only one institution so that it could not be verified whether these same training characteristics and teaching practices arise in research in other educational institute. Future research may be conducted to deepen the teaching practice, specifically that of tutoring in E-learning as well as the exercise of teaching by professionals from the Bachelor's degree.